Selling a Resume and Buying a Job: Stratification of Gender and Occupation by States and Brokers in International Migration from Indonesia. (1st March 2021) - Chang, Andy Scott
Abstract: This study examines how state and commercial actors construct gender, occupation, and nationality hierarchies in guest worker programs by comparing the migratory procedures for female domestic workers and male industrial operators from Indonesia. Based on 19 months of multi-sited ethnography and 86 interviews in Indonesia, Taiwan, and Singapore, I introduce the notion of multilateralism to theorize the stratification of global migration processes. In multilateral labor markets, governments, brokers, employers, and migrants in multiple countries contend for labor and employment. The homecare market is governed under the rubric of "selling a resume, " whereby Indonesian regulators and labor suppliers pass on recruitment costs to employers, in a context where migrant domestics possess myriad destination options due to their reputation fostered by a government-organized credentialing program. By contrast, Indonesian factory workers expend upfront payment to "buy a job" from destination brokers amid rivalry with migrants of other nationalities. The Indonesian state's inattention to elevating industrial migrants' standing through skill formation has compelled private recruiters to vie for jobs by extracting brokerage fees and developing a patchwork of selection mechanisms. This article finds that social actors' capacity to negotiate the terms of labor exchange is contingent on their structural locations within a global hierarchy of competing nation-states.